The Impact of Scour on Laterally Loaded Piles Bored and Socketed in Marine Clay - Chentao Li; Yang Xiao; Jieqing Liu; Qingwei Lin; Taotao Zhang; Jiaming Liu (Journal of Marine Science and Engineering, 2022)
The majority of long-span bridges and offshore construction in deep water are supported by bored pile foundations. Pile foundations under water will be susceptible to scour, which will pose a significant danger to their safe operation. A three-dimensional finite element (FE) numerical analysis was conducted to examine the influence of scour on the responses of laterally loaded drilled piles in marine clays. First, the FE numerical model was calibrated using field test data of a drilled pile that did not include scour in soft marine clay. The findings of numerical modeling reveal that scour decreases the ultimate lateral capacity of socketed drilled piles, with the percentage of reduction being strongly related to scour types and depth, but moderately related to scour hole width and slope angle. Finally, a semi-empirical formula for calculating the effects of scour on the lateral capacity of socketed drilled piles following scour is presented. This method may be utilized fast and effectively to calculate scour’s effects.